TopFuel'97. (Thomas Telford, 1997)
While fuel cycle economics continue to be determined by the design and fabrication costs of fuel manufacture and its in-core performance, the issue of the reuse of separated plutonium has now added a further dimension to the total technical/economic picture. In this work, current trends in advanced fuel designs are described together with details of developments in more efficient fuels and improved materials for all the major reactor types in Europe, USA and Japan.
Keywords: Nuclear fuels -- Congresses.; elektronické knihy; electronic books